2020
DOI: 10.1021/acsbiomaterials.0c00156
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Tensile Properties of Wet Spun Silk Fibers Using Rapid Bayesian Algorithm

Abstract: Wet spinning of silkworm silk has the potential to overcome the limitations of the natural spinning process, producing fibers with exceptional mechanical properties. However, the complexity of the extraction and spinning processes have meant that this potential has so far not been realized. The choice of silk processing parameters, including fiber degumming, dissolving, and concentration, are critical in producing a sufficiently viscous dope, while avoiding silk’s natural tendency to gel via self-assembly. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…In addition, such efforts are yet to include a quantitative discussion of process energy efficiency, a topic becoming increasingly important from both an industrial and consumer perspective. [ 4,5 ]…”
Section: Introductionmentioning
confidence: 99%
“…In addition, such efforts are yet to include a quantitative discussion of process energy efficiency, a topic becoming increasingly important from both an industrial and consumer perspective. [ 4,5 ]…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, aqueous silk fibroin solutions were also prepared from the same B. mori silk source to ensure optimal interactions upon mixing with SN. We used our previously developed dissolution protocol [ 33 ] to produce silk fibroin of different chain lengths (i.e., 33 and 184 kDa, as determined using size exclusion HPLC [ 22 ] ). After several iterations of silk dope preparation, we found that the SN must first be dispersed using 33 kDa silk fibroin prior to its addition to a 184 kDa silk fibroin solution ( Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…A detailed description of how these preparation conditions produce silk with these molecular weights can be found in the previous work. [ 33 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations